Reading the Ironic Layers of the (Re)construction: The Colony and its (Colonial?) Others in the Construct of “Austrian Bosnia” in The Bridge on Drina River BY iVO ANDRIĆ - Škvorc, Boris (Porównania, 2015)
This text offers a reading of Ivo Andrić’s novel The Bridge on Drina River (1945) placing special emphasis on the economies of utterance and the (re)construction of sto-ry/myth produced from the position of various native informants at the level of authorial intent. It argues that the position of colonial subjects/objects in the novel, as uttered and emphasised by Andrić could best be read from a post-colonial perspective. That opens two possibilities of reading Andrić and South Slavic historical novels in general. The first one concerns the understanding of space of the South European narration/stereotyping as the space of imperial/colonial power games. The second one deals with consequences of that presumption and appropriation of histori-cal realms that deal with the space of narration in connection with various latter naturalisation of the text(s). The emphasis is put on Andrić’s novel. However, this reading of the text’s construc-tions also opens the way of re-reading other “historical” novels and their ideological/political constructs in South Slavic and wider Central European/Eastern European context/discourse.